The image of human rights in e-state - Susi, Mart (Journal of the Belarusian State University. International Relations, 2020)
The article applies the non-coherence theory of digital human rights to e-statehood and identifies five caveats. The emerging image is characterized by the absence of human rights rhetoric from e-state goals and strategy, absence of conclusive justification of e-state success in social context, relatively lower protection of human rights through e-state solutions in comparison with solutions in the private digital domain, dichotomy of the meaning of privacy in the digital domain, and the theoretical threat of e-state transforming into a police-state. The article argues that since human rights are not generic to e-state, their inclusion into the rhetoric about e-state is the result of public pressure. The author proposes the thesis about negative correlation between the e-state and human rights: the expansion of e-state solutions in a given society leads to decrease in fundamental rights protection.